Assessing the impact of green transformation on carbon emissions: a dynamic spatial Durbin model - Peng Gao; Chao Qu (Frontiers in Environmental Economics)
IntroductionChina's environmental policies and the green transformation of its industries have attained paramount significance in the wake of intensifying climate change and soaring carbon emissions, critically shaping sustainable development at both national and international scales. As the exploration of the drivers and outcomes of this green revolution on carbon emissions gains traction as a focal point of research, this study endeavors to assess the effects and their underlying causes.MethodsUtilizing a systems thinking methodology, a dynamic spatial Durbin model was constructed, analyzing statistical data spanning from 2004 to 2021, encompassing 30 Chinese provinces.ResultsChina's green transformation significantly influences the spatial distribution patterns of carbon emissions across various regions.DiscussionEnvironmental Protection investment has been effective in curbing carbon emissions from local businesses, yet it may also prompt a relocation of these businesses to neighboring provinces, inadvertently elevating their carbon emissions. Green innovation and the adoption of green energy technologies have proven instrumental in reducing carbon emissions in a region, with positive spillover effects extending to nearby areas. The dynamic spatial Durbin model analysis further underscores the inertia of carbon emissions, indicating that achieving carbon reduction is a process requiring consistent and sustained efforts over the long term. The findings of this study offer valuable insights and recommendations for the government in devising and implementing green transformation policies that align with the dual-carbon target, aiming to achieve a greener and more sustainable future.